The Correlation Between Note-Taking Practice and Writing Ability at Grade XI of Students SMK Bina Insan Siak Hulu - Silva Iriana Widari; Ardiya Ardiya; Qonaah Nuryan Arif (SOKO GURU: Jurnal Ilmu Pendidikan, 2025)
This research examines the correlation between note-taking practice and writing ability among grade XI students at SMK Bina Insan Siak Hulu. The research was motivated by the fact that students in this school do not own personal textbooks and relay heavily on their notes as the main source of independent study. This research employed a quantitative correlational design. The population consisted of 36 grade XI students, who were also taken as the total sample. Data were collected using two instruments that is a note-taking practice questionnaire, and a writing test in the form of a descriptive text task assessed with an analytic rubric. Data analysis was carried out using Pearson Product Moment Correlation through SPSS version 23 after conducting validity, reliability, normality, and linearity test. The results revealed that the Pearson correlation coefficient between note-taking practice and writing ability was r = 0.275 with a significance value of 0.105. This indicates a weak positive correlation that is not statistically significant. So that, Ha or the researcher’s assumption is rejected. In other words, students’ note-taking practice did not show a significant influence on their writing ability. Thus, it can be concluded that there is no significant correlation between note-taking practice and writing ability among grade XI of students SMK Bina Insan Siak Hulu.